2021
DOI: 10.1007/s10570-021-03804-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving the accuracy of estimating paper permanence for accelerated degradation in closed vials

Abstract: To more accurately predict the permanence of paper during natural aging, we studied cellulose aging according to closed vial setup, which compared to alternative paper aging methods is closer to natural aging with regard to predictions of paper life expectancy. To improve kinetic evaluation, not only cellulose degradation by hydrolysis and oxidation, but also the moisture content in the closed vial were measured during the aging process. This allowed to eliminate the long-known errors of the method caused by v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Whatman paper is 100% pulp, a material susceptible to oxidation and hydrolysis at increased temperature and humidity, manifested by a decrease in the degree of substitution and the release of furan derivatives and organic acids [ 31 , 35 , 36 , 37 ]. A considerable change of color, caused, above all, by yellowing, was recorded after separate aging of the Whatman paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whatman paper is 100% pulp, a material susceptible to oxidation and hydrolysis at increased temperature and humidity, manifested by a decrease in the degree of substitution and the release of furan derivatives and organic acids [ 31 , 35 , 36 , 37 ]. A considerable change of color, caused, above all, by yellowing, was recorded after separate aging of the Whatman paper.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest pH of a cold extract in the sample from the white foam sandwich may be caused by the absorption of acids released from the white foam by the paper or by a greater extent of paper degradation caused by the effect of a higher concentration of acidic substances [ 37 ]. In the presence of moisture, an acidic environment supports acid hydrolysis of cellulose, which manifests itself above all by a shortening of the polymeric chain [ 31 , 32 , 35 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This difference is significant regarding the fact that 4 hygro buttons, two in two tubes, recorded the same variation with an accuracy of 0.5 % RH. Interestingly, other authors showed an important drop of RH during ageing in closed vials at similar temperature, with a decrease of 30 % in 80 days at 65 °C (Jeong & Potthast, 2021). They linked this decrease with the presence of water vapour flows outside the closed vials and, as the concentration in water influences the hydrolysis rate, they proposed a recalculation method to account for the loss of water.…”
Section: Monitoring Of the Relative Humidity Inside The Tubesmentioning
confidence: 99%
“…However, tightening of the tubes must be adequate because leakage of humidity can occur. Some authors propose to monitor the weight of the tubes during the ageing to evaluate the possible flows of humidity and to correct the actual hygrothermal conditions with time (Jeong & Potthast, 2021;Sawoszczuk et al, 2008). Here, to ensure trustworthy experimental results, we evaluated the robustness and reliability of the accelerated ageing technique in closed tubes beforehand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation